Islam dan Praktik Pemberdayaan Perempuan: Studi terhadap Implementasi Nilai-Nilai Islam dalam Pemberdayaan Perempuan oleh Yayasan Sahabat Ibu di Yogyakarta - Widianto, Ahmad Arif (Asketik: Jurnal Agama dan Perubahan Sosial, 2017)
The emergence of non-governmental organizations (NGOs) actively empowering women can supplement the lack of implementation of the program of empowerment from the Government. Despite all its shortcomings, a previous Study demonstrated that NGOs are more effective in carrying out empowerment programs with a variety of models and strategies. Mother’s best friend Foundation (YSI) undertook to actively empower women in Yogyakarta and mengooptasi way to implement Islamic values not only on a theoretical level but also practical. This paper discusses how YSI implements Islamic values and the implications for how the process of empowerment. This research uses the qualitative approach method of verstehen to interpret the subject’s understanding of research on Islamic-based empowerment. Data collection techniques using participatory observation and in-depth interviews against informants chosen purposively. The results showed that the application of the values of Islam is more of an approach at once an instrument of women’s empowerment. Islamic practices are applied in the empowerment of such as contracts, pledges, pengajian, and infaq can push the lancarnya through the process of empowerment. The subject of research looked at that program of empowerment is the obligation to family and God. Nevertheless, there are several members resigned because the program prove incriminating. On the one hand, the implementation of Islamic values becomes the driving force of empowerment, and on the other hand, gives rise to a difference of views among the participants and facilitator so it becomes counterproductive.